Migraines prevalence and its relationship with crane mandible’s asymmetries in 6 to 13 year-old children - Meza Sevillano, Darío (2008)
The purpose of the study was to determine the existence of a relationship between the primary migraines and the macroscopic face asymmetries in patients of 6 to 13 years of Dental Faculty of San Marcos University. In order to determine the prevalence of migraine in the pediatric population a test with the criteria of macroscopic IHS 2004 was used and the facial asymmetry were divided in soft weave Asymmetries and hard weave Asymmetries. For the first the photograph method was used, and panoramic x-rays with the technique of panorograma of Simoes symmetry for the second. The children Migraines prevalence was 34.78% appearing more in girls than boys with a 1.66 relation. The prevalence of soft weave asymmetry was of 42.03% increasing with age. There was not statistically significant relation between soft weave asymmetry and migraine (p> 0.05). The hard weave asymmetry was of 77.54%. There was a statistical significant relation between hard weave asymmetry and migraines (p < 0.05).